Breakup of Liquid Jets. (January 2016) - Omocea, Ioana Laura; Patrascu, Claudiu; Turcanu, Mihaela; Balan, Corneliu
Abstract: The present paper investigates breakup of immersed jets of water and water - glycerol solutions in a hydrophobic environment. Organic oil was used as the surrounding medium. Experimental setup allowed the investigation of jet behavior, respectively the exact moment when perturbations appear. The phenomenon of jet breakup was quantified by measuring the breakup length. Maximum breakup length, normalized with the nozzle diameter, was plotted and analyzed function of dimensionless numbers. Results showed that normalized breakup length has a linear dependence with Reynolds and Capillary, respectively.